Human rights to Internet access and its safe use - V. V. Popov; P. I. Moskalenko; S. V. Cherkasova (Вестник университета)
This work is devoted to the analysis of the right to access the Internet and its safe use. The main purpose of the article is to consider the right to access the Internet and to a favorable social environment, as well as the introduction of these rights into the legislation of the Russian Federation. The authors analyzed the legislation of various states and international organizations in the field of free Internet access, considered the impact of a favorable Internet environment on the human psyche. The object of the study is the subjective human rights to access the Internet and to use the Internet safely. The subject of the study is the legal norms of the Russian Federation and foreign states, the norms of international law. The authors consider the role of a favorable environment on the Internet for minors, describe the main factors of restrictions on access to the Internet for teenagers. The methodological and theoretical basis of the research are private and general scientific approaches to the study of this topic. Formal logical and comparative methods were used, as well as methods of structural analysis. During the study, conclusions about the main differences in approaches to digital rights in the Russian Federation, foreign legal systems, and international law were drawn.